Emprego da microextração líquido-líquido dispersiva em fase reversa para o preparo de amostras de óleo de coco para determinação de metais por ICP-OES - Prado, Leandra Muller do (2022)
Coconut oil is a healthy food and is also widely used in cooking and as a nutraceutical product. However, contamination with heavy metals in coconut oil may occur from fertilizers, soil exposure to environmental contamination, and oil extraction and refining processes. Thus, the National Health Surveillance Agency (ANVISA), according to international trends, establishes maximum limits for various metals in oily or fatty foods. Coconut oil may be in a liquid or solid state depending on its composition and ambient temperature, which makes it difficult to handle in sample preparation procedures. Therefore, the reversephase dispersive liquidliquid microextraction method (RPDLLME) was applied in the preparation of the coconut oil sample for microextraction and preconcentration of metals. The analytes were determined by inductively coupled plasma optical emission spectrometry (ICP OES). Innovatively, in the preparation of the samples, a green solvent Dlimonene was first added to maintain the liquid phase. In extract, a mixture of two solvents, a dispersant (npropanol) and a sampler (diluted HNO3), is added to a tube containing 5 g of coconut oil diluted with Dlimonene, already heated. Then, the samples were shaken and centrifuged to extract the phase. Extracted and preconcentrated analytes (Al, Ba, Cd, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Pb, Ti, V, Zn) were determined by ICP OES. The parameters evaluated for the method optimization were the type of dispersing solvent (ethanol, propanol, isopropanol); the dispersing solvent ratio (50:50:40, 70:30, and 80:20 (v v 1 )), extractor volume and concentration, and agitation time. The proposed method presented analysis recovery ranging from 81 to 106% (RSD < 6%). The evaluation of how green the proposed RPDLLME method was performed using AGREE® software to measure Green Chemistry measurements. The method developed was considered suitable for the determination of trace metals and edible coconut oil, following the Principles of Green Analytical Chemistry. The proposed RPDLLME method is characterized by fast and simple operation, high sample mass, low reagent consumption, lesser particle generation, and high frequency analysis. Finally, the method is proved to be feasible, being the first application of RPDLLME for coconut oil combined with the use of Dlimonene and subsequent determination by ICP OES.